Determinação de cádmio, cobre e chumbo em batata produzida na região de Guarapuava-PR, utilizando técnica voltamétrica - Bochnia, Lislaine Pilati (2010)
This work is the key point in determination of traces of toxic in potatoes produced and marketed in the region of Guarapuava-PR. Some metallic elements cause impacts on human health, primarily through the diet that is the source of all substrates and elements necessary for human metabolism. The choice of potato as vegetable of reference is that it is cultivated in the region of Guarapuava-PR, due to the mild climate and fertile soils. Currently, the region grows about 4000 ha / year of the potato. The potato tuber is well protected by a dermal tissue (bark), with high firmness. This property gives the potato a measure of protection to water loss and a high resistance to impact and abrasions. The potato is one of the most nutritious food for humans, has good quality protein content and high biological value, being one of the most tubers consumed by brazilians. The soil has a very peculiar characteristic linked to various spheres that affect human life. It is also the main substrate for the production of food and a major source of nutrients to be absorbed by plants. The trace metals Cd, Cu and Pb, has attracted interest as investigations to better understand its mechanisms of toxicity and to determine its concentration and to assess possible environmental problems. The voltammetric technique is widely used for analytical purposes, it is currently the stripping voltammetry, the relevant method in trace analysis, especially in the determination of metals such as lead, cadmium, zinc and copper in samples of environmental interest, because of its low cost, simplicity and low detection limits. Based on the chemical analysis it was observed that the concentration of trace elements of interest were within the tolerance limit (LMT) allow by law, demonstrating that it is of paramount importance in the monitoring of food samples and is of vital importance in reviewing the plant development and in the diagnosis of food contamination. Also, provide the information about issues of agricultural and environmental contamination, providing internalizing so a study of possible indicators of contamination, health risks, thereby contributing to the social, scientific and technological in the country.